A review of the genus Gargela Walker in China, with descriptions of ten new species (Lepidoptera: Crambidae, Crambinae) - Song, Shimei; Chen, Fuqiang; Wu, Chunsheng (Zootaxa, 2009)
The present paper reports twelve species of the genus Gargela Walker from China. Ten species are reported as new to science, named herein G. bilineata, G. distigma, G. hastatela, G. xizangensis, G. hainana, G. albidusa, G. quadrispinula, G. furca, G. fuscusa, G. minuta. The adults and genital structures of new species are described, with photographs of the adults and illustrations of genitalia. A key to the Chinese species, based on male specimens is provided.